The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1007/s00436-023-08050-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to the diagnosis of Contracaecum magnipapillatum infections in Australian black noddies, Anous minutus (Charadriiformes: Laridae)

Shokoofeh Shamsi,
Leanne Nelson,
Anita Gordon
et al.

Abstract: We provide the incidental necropsy findings associated with anisakid nematode infections of black noddy terns, Anous minutus Boie, 1844 (Charadriiformes: Laridae), from offshore islands in the southern Great Barrier Reef, Queensland, Australia. Specimens collected from the proventriculi were identified morphologically as Contracaecum magnipapillatum Chapin, 1925 (Rhabditida: Anisakidae), using light and scanning electron microscopy (SEM). The entire nuclear ribosomal DNA internal transcribed spacer (ITS) regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Dos Santos and Avenant-Oldewage (2020) reviewed currently available genetic data, to uncover insights from the current sequence data, suggested improvements for future studies, and highlighted potential pitfalls to be avoided. Like several other studies about other parasitic taxa (Barton et al 2022;Shamsi et al 2024), Dos Santos and Avenant-Oldewage (2020) pleaded for a more integrated taxonomic approach and the inclusion of voucher material alongside the sequence data obtained from several additional markers, and concluded that analyses of a substantial amount of further morphological and genetic data are needed before an accurate study of the taxonomy and evolutionary history of diplozoid species can be achieved. These challenges over specific identification of the existing taxa makes introducing a new species challenging.…”
Section: Discussionmentioning
confidence: 94%
“…Dos Santos and Avenant-Oldewage (2020) reviewed currently available genetic data, to uncover insights from the current sequence data, suggested improvements for future studies, and highlighted potential pitfalls to be avoided. Like several other studies about other parasitic taxa (Barton et al 2022;Shamsi et al 2024), Dos Santos and Avenant-Oldewage (2020) pleaded for a more integrated taxonomic approach and the inclusion of voucher material alongside the sequence data obtained from several additional markers, and concluded that analyses of a substantial amount of further morphological and genetic data are needed before an accurate study of the taxonomy and evolutionary history of diplozoid species can be achieved. These challenges over specific identification of the existing taxa makes introducing a new species challenging.…”
Section: Discussionmentioning
confidence: 94%